Decoupling hydrodynamic and entanglement effects on the modulus reinforcement of grafted silica filled nanocomposites through Thermal and rheological features. (20th January 2021) - You, Wei; Cui, Wenzhi; Yu, Wei
Abstract: To provide insights into how nanoparticles (NPs) with different graft structures affect the moduli of polymer nanocomposites (PNCs), we have performed various surface modifications on silica nanoparticles, including the grafted small molecules, the long low-density grafted chains, and the cross-linked grafted shell. The nanoparticles can be well dispersed in a polymethyl methacrylate (PMMA) matrix using suitable mixing methods, and the inter-particle surface to surface distance follows the modified Woodcock model. The interfacial layer volume fraction was studied by the temperature-modulated differential scanning calorimetry (TMDSC), which showed a non-monotone variation with the increase of particle concentrations in the long low-density grafted particles filled PNCs. The effective interfacial thickness was also determined from the hydrodynamic enhancement of the rubbery plateau modulus at low particle loadings, which is smaller than that from TMDSC. The matrix entanglement contribution was then decoupled from the hydrodynamic contribution and the confined diffusion of nanoparticles. The change of mean tube diameter of polymer chains appeared when the interparticle surface to surface distance became comparable to the unconfined tube diameter. By adjusting the grafting phase structures, the interface structures, and the rubbery modulus of PNCs can be effectively controlled. Graphical abstract: Image 1 Highlights: Balance between hydrodynamic and entanglement effects on modulus has been identified. Entanglement effect dominates the modulus enhancement under high particle load. Rheological model was developed to estimate the tube diameter in PNCs.